Vehicle-mounted high-voltage-resistant MLCC ceramic powder and preparation method and application thereof

By using high-voltage MLCC ceramic powder prepared by nano powder and specific doped materials, the insufficient performance of existing MLCC materials under high-voltage and high-temperature conditions is solved, and the high-voltage and high-temperature stability of ceramic capacitors is achieved, meeting the requirements of X8R grade.

CN119874352AInactive Publication Date: 2025-04-25HANGZHOU XINGRONG TECH CO LTD
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
CN202510371445.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing MLCC materials are difficult to meet the technical requirements of X8R grade under high pressure resistance requirements, especially in high temperature conditions, and their performance is poor.

Method used

Vehicle-based high-voltage MLCC porcelain powder made of nanopowders and doped materials (including lithium fluoride, magnesium oxide, silica, trimanium tetrade oxide, yttrium oxide, yttrium oxide and vanadium pentoxide) improves the voltage withstand and high temperature stability of ceramic capacitors through specific preparation methods and sintering processes.

Benefits of technology

It realizes the high voltage resistance and high temperature stability of MLCC, can maintain stable operating performance within the temperature range of -55°C to 150°C, meets the requirements of X8R grade, and is suitable for high-demand fields such as on-board electronic systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874352A_ABST
    Figure CN119874352A_ABST
Patent Text Reader

Abstract

The invention discloses vehicle-mounted high-voltage-resistant MLCC (multilayer ceramic capacitor) ceramic powder as well as a preparation method and application thereof. The invention provides vehicle-mounted high-voltage-resistant MLCC (multilayer ceramic capacitor) ceramic powder which is prepared from the following raw materials: # imgabs 0 # nano powder, # imgabs 1 # nano powder and a doping material, and the doping material comprises lithium fluoride, magnesium oxide, silicon dioxide, manganous-manganic oxide, yttrium oxide, ytterbium oxide and vanadium pentoxide. The vehicle-mounted high-voltage-resistant MLCC ceramic powder has stable dielectric properties in a wide temperature range of X8R standards, also has high breakdown strength, and is suitable for high-temperature and high-voltage working environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electronic materials, and in particular to a high-voltage MLCC ceramic powder for vehicle use, a preparation method thereof, and applications thereof. Background Art

[0002] With the rapid development of automotive electronic technology, especially in the promotion and application of electric vehicles and hybrid vehicles, the reliability and performance requirements of on-board electronic equipment are increasing. Multilayer ceramic capacitors (MLCC) are widely used in automotive electronic circuits due to their excellent electrical performance and miniaturization characteristics, especially in key areas such as power management, signal processing and battery management systems.

[0003] However, the performance of traditional MLCC in high-voltage applications still has certain limitations. Existing ceramic capacitors often face challenges of high voltage shocks and transient voltages in actual use, especially in electric vehicles and high-voltage power systems, which makes the voltage resistance of capacitors one of the important factors affecting their reliability. For automotive electronic equipment, the failure of capacitors will not only cause circuit malfunctions, but may also cause safety hazards, seriously affecting the safety and stability of the entire vehicle.

[0004] At present, although there are some methods for preparing high-voltage MLCCs, which have improved the voltage rating of capacitors to a certain extent, for example, domestic patent CN119430912A reported a dielectric ceramic material for preparing medium- and high-voltage X7R MLCCs, and CN112723876A reported a breakdown voltage of 6.2 kV that meets the X7R MLCC material. Despite this, there are no reports of high-voltage MLCCs that meet the X8R application standard (-55°C to +150°C temperature range, ±15% capacitance tolerance) in the prior art, and the performance of dielectric ceramic capacitors under high temperature conditions still needs to be improved.

[0005] Therefore, there is an urgent need to develop a new high-voltage MLCC ceramic powder for automotive use that meets the technical requirements of the X8R level, so as to improve the voltage resistance of ceramic capacitors while ensuring their safety and reliability in high-temperature working environments, thereby meeting the higher performance requirements of modern automotive electronic systems. Summary of the invention

[0006] The technical problem to be solved by the present invention is that the MLCC materials in the prior art are difficult to meet the technical requirements of the X8R grade under the high voltage resistance requirements. To this end, the present invention provides a high voltage MLCC ceramic powder for vehicle use, a preparation method thereof and its application. The MLCC ceramic powder provided by the present invention can meet the technical requirements of the X8R grade while having high voltage resistance performance of the MLCC.

[0007] The present invention provides a high-voltage MLCC ceramic powder for vehicle use, which is made of the following raw materials: Nano powder, Nano powder and doping material, wherein the doping material includes lithium fluoride, magnesium oxide, silicon dioxide, manganese tetraoxide, yttrium oxide, ytterbium oxide and vanadium pentoxide.

[0008] In the present invention, optionally, the amount of doping material added is The dosage is the basis and the measurement is 1 or 100%.

[0009] In the present invention, optionally, in the doping material, the added amount of lithium fluoride is 4 to 6 mol%.

[0010] In the present invention, optionally, in the doping material, the added amount of magnesium oxide is 4 to 6 mol%.

[0011] In the present invention, optionally, the added amount of silicon dioxide is 1 to 3 mol%.

[0012] In the present invention, optionally, the added amount of trimanganese tetraoxide is 0.1 to 0.3 mol%.

[0013] In the present invention, optionally, the added amount of yttrium oxide is 1 to 3 mol%.

[0014] In the present invention, optionally, the added amount of ytterbium oxide is 1 to 3 mol%.

[0015] In the present invention, optionally, the added amount of vanadium pentoxide is 0.1 to 0.3 mol%.

[0016] In the present invention, optionally, the The addition amount of nano powder is 1 to 3 mol%.

[0017] In the present invention, optionally, the The addition amount of nano powder is 80-90 mol%.

[0018] In the present invention, optionally, the The nanopowder is prepared by the following method: calcium nitrate tetrahydrate and tetraisopropyl titanate are mixed in a molar ratio of 1:1, deionized water is added, and the precursor liquid is stirred evenly to form a precursor liquid; the precursor liquid is transferred to an autoclave, reacted at 200°C for 12 hours, cooled after the reaction, centrifuged, and washed; and then dried at 80°C for 12 hours to obtain the Nano powder.

[0019] In the present invention, optionally, the The nanopowder is prepared by the following method: four solutions A, B, C and D are prepared, wherein solution A is a solution prepared by dissolving 2.5 g of barium acetate in 50 ml of deionized water; solution B is a solution prepared by adding 5 g of sodium hydroxide into 50 ml of deionized water; solution C is a solution prepared by dissolving 2.83 g of tetraisopropyl titanate in 50 ml of anhydrous isopropanol; and solution D is a solution prepared by dissolving 25 ml of oleic acid in 50 ml of anhydrous isopropanol.

[0020] Then, solution A and solution B were mixed, and the pH value of the mixed solution was adjusted to 14; then, solution C containing a titanium precursor was added dropwise to the mixed solution; finally, solution D containing oleic acid was added to the mixed solution; after vigorous stirring, the mixture was transferred to an autoclave and reacted at 180° C. for 16 hours; after the reaction, the mixture was centrifuged, the precipitate was washed with ethanol, and then dried at 80° C. for 12 hours to obtain the Nano powder.

[0021] The present invention also provides a method for preparing a high-voltage MLCC ceramic powder for use in vehicles, which comprises the following steps: (1) Nano powder and the The nano powders are mixed, and then the doping material is added to form a mixed powder. The mixed powder is then placed in an oven and pre-dried at 80° C. for 12 hours to obtain a pre-dried mixed powder.

[0022] (2) The obtained pre-dried mixed powder, zirconium oxide balls and anhydrous ethanol are mixed in a weight ratio of 1:6:3, and ball-milled on a planetary ball mill; the ball milling time is 24 hours, and the rotation speed is 300 r / min. The slurry obtained after ball milling is vacuum dried at 100°C for 12 hours to obtain a dry high-voltage MLCC ceramic powder; wherein the doping material includes lithium fluoride, magnesium oxide, silicon dioxide, manganese tetraoxide, yttrium oxide, ytterbium oxide and vanadium pentoxide.

[0023] The present invention also provides a multilayer ceramic capacitor, which is manufactured by sintering the high-voltage MLCC ceramic powder as described above.

[0024] In the present invention, the multilayer ceramic capacitor is made by sintering high-voltage MLCC ceramic powder and metal inner electrodes; wherein the sintering temperature is 1150°C to 1250°C, the sintering time is 2 to 4 hours, the thickness of the dielectric layer is 6 to 8 μm, and the number of layers is 100 to 140.

[0025] The present invention also provides the above-mentioned high-voltage MLCC ceramic powder for application in vehicle-mounted electronic systems.

[0026] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0027] The reagents and raw materials used in the present invention are commercially available.

[0028] The positive progress of the present invention is that a MLCC ceramic powder for automotive use with high withstand voltage and excellent high temperature stability is obtained. The multilayer ceramic capacitor prepared by the ceramic powder has both high voltage resistance and high temperature working stability, can maintain stable working performance in a wide temperature range of -55°C to 150°C, meets the requirements of X8R grade, has good application prospects, and is particularly suitable for high-demand fields such as automotive electronic systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 For Example 1 of the present invention Scanning electron micrograph of nanopowder.

[0030] Figure 2 For Example 2 of the present invention Scanning electron micrograph of nanopowder.

[0031] Figure 3 This is a dielectric temperature diagram obtained by testing MLCC sample A of Example 3 of the present invention in the temperature range of -55°C to 200°C.

[0032] Figure 4 This is a dielectric temperature diagram obtained by testing MLCC sample B of Example 4 of the present invention in the temperature range of -55°C to 200°C.

[0033] Figure 5 This is a Weibull distribution diagram of the breakdown strength of MLCC sample A according to Example 3 of the present invention.

[0034] Figure 6 This is a Weibull distribution diagram of the breakdown strength of MLCC sample B according to Example 4 of the present invention. DETAILED DESCRIPTION

[0035] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0036] Embodiment 1: Preparation of nanopowders.

[0037] Mix 10 g of calcium nitrate tetrahydrate (Ca(NO3)2·4H2O) and 12 g of tetraisopropyl titanate in a molar ratio of 1:1, add 100 ml of deionized water, and stir evenly with a magnetic stirrer to ensure that the solution is fully mixed to form a uniform precursor liquid. Transfer the precursor liquid to a 500 ml Teflon-lined autoclave and react at 200°C for 12 hours. After the reaction is completed, the reaction product is cooled, centrifuged, and washed with deionized water. Then dry at 80°C for 12 hours to obtain Nano powder. The powder is sent to the scanning electron microscope for testing, such as Figure 1 As shown. Figure 1 Knowable Nanopowders are spherical particles with an average particle size of about 150nm.

[0038] Embodiment 2: Preparation of nanopowders.

[0039] Prepare the following four solutions: Solution A is a solution of 2.5 grams of barium acetate dissolved in 50 milliliters of deionized water; Solution B is a solution made by adding 5 grams of sodium hydroxide to 50 milliliters of deionized water; Solution C is a solution of 2.83 grams of tetraisopropyl titanate dissolved in 50 milliliters of anhydrous isopropanol; Solution D is a solution of 25 milliliters of oleic acid dissolved in 50 milliliters of anhydrous isopropanol. First, mix solution A and solution B, and adjust the pH value of the mixture to 14, at which time a white precipitate will be formed. Subsequently, solution C containing the titanium precursor is added dropwise to the above mixture. Finally, solution D containing oleic acid is added to the mixture to form a white creamy suspension. Subsequently, the suspension is vigorously stirred for 30 minutes and transferred to a 500-ml Teflon-lined autoclave. React at 180°C for 16 hours. After the reaction is completed, the precipitate is separated by centrifugation, washed with ethanol, and then dried at 80°C for 12 hours to obtain Nano powder. The powder is sent to the scanning electron microscope for testing, such as Figure 2 As shown. Figure 2 Knowable Nanopowders are cubic particles with an average particle size of about 200 nanometers.

[0040] Example 3: Preparation of MLCC sample A.

[0041] Weigh 10 grams of the prepared Nanopowders and Nano powder mixing, then refer to The following components were added in molar amounts: 5 mol% lithium fluoride (LiF), 2 mol% magnesium oxide (MgO), 2 mol% silicon dioxide (SiO2), 0.2 mol% manganese tetraoxide (Mn3O4), 2 mol% yttrium oxide (Y2O3), 2 mol% ytterbium oxide (Yb2O3), and 0.2 mol% vanadium pentoxide (V2O5). Subsequently, the mixed powders were placed in an oven and pre-dried at 80°C for 12 hours to remove moisture from the raw materials. The pre-dried raw materials, zirconium oxide balls and ball milling media anhydrous ethanol were mixed in a weight ratio of 1:6:3 and ball milled on a planetary ball mill. The ball milling time was 24 hours and the rotation speed was 300 r / min. The slurry obtained after ball milling was vacuum dried at 100°C for 12 hours to obtain a dry dielectric ceramic powder.

[0042] The obtained dielectric ceramic powder is made into slurry. The slurry is then processed into a dielectric raw magnetic diaphragm by tape casting technology. Then, a screen printer is used to print nickel alloy electrodes on the surface of the diaphragm with nickel paste, and the diaphragm and the inner electrode are superimposed to form a laminated structure. By alternately printing the dielectric film of the inner electrode, a laminated sheet is finally constructed. Next, after isostatic pressing, the green body is cut into the desired shape. The green body is then sintered in a nitrogen atmosphere at 1180°C for 4 hours. Then the temperature is lowered to 1000°C and maintained for 1 hour, and finally the temperature is lowered to room temperature to obtain a ceramic body. The two ends of the obtained ceramic body are chamfered, and after being coated with copper paste, they are sintered at 900°C to form a copper alloy external electrode firmly bonded to the ceramic body, and then nickel and tin layers are electroplated on the surface of the copper electrode, respectively, to finally obtain MLCC sample A. The thickness of the dielectric layer of the obtained MLCC sample A is 7 μm, and the number of layers is 120.

[0043] Example 4: Preparation of MLCC sample B.

[0044] The preparation method of this embodiment is basically the same as that of embodiment 3, except that 5 mol% lithium fluoride is not added. Finally, MLCC sample B is obtained. The thickness of the dielectric layer of the obtained MLCC sample B is 7 μm, and the number of layers is 120.

[0045] Example 5: Performance test of MLCC samples.

[0046] The obtained MLCC samples A and B were tested for capacitance-temperature change rate and dielectric properties. The test conditions were: test frequency of 1kHz and test temperature range of -55℃~200℃. The test results are as follows: Figure 3 and Figure 4 shown.

[0047] According to the conditions of Example 3 and Example 4, 10 MLCC samples were prepared respectively, and the samples were subjected to breakdown strength test using a ZJC-50E voltage breakdown tester. The test conditions were: the initial load voltage was 1 kV, and the voltage increase rate was 3 kV / s. The obtained Weibull distribution diagram is shown in the figure below: Figure 5 and Figure 6 shown.

[0048] Depend on Figure 3 and Figure 4 It can be seen that both sample A and sample B show relatively stable capacitance changes. In the range of low temperature (-55°C) to high temperature (150°C), the dielectric constant changes slightly, indicating that they both have good temperature stability and can meet the requirements of the X8R standard.

[0049] Weibull distribution of voltage breakdown strength Figure 3 and Figure 4 It can be seen that the breakdown strength distribution of the MLCC samples prepared according to Example 3 is relatively concentrated, all greater than 66.1 kV / mm, indicating that the MLCC samples prepared according to Example 3 have a higher breakdown voltage stability and a stronger breakdown strength, and are suitable for use in electrical equipment in high-voltage environments. The breakdown strength of the MLCC sample 34.3 k-36.4 kV / product prepared according to Example 4 is somewhat different from that of the sample in Example 3, the breakdown strength is between mm, and the pressure resistance is reduced. The reason for the analysis is that the addition of LiF can greatly improve the breakdown resistance, which is attributed to the grain boundary effect formed by the segregation of favorable defects such as oxygen vacancies at the grain boundaries, thereby effectively hindering the free movement of charged ions.

[0050] Based on the test results of capacitance-temperature change rate and voltage breakdown strength, the MLCC sample prepared in Example 3 performs well in temperature stability and breakdown strength, meets the requirements of the X8R standard, and is suitable for applications with high temperature and high voltage. Although the MLCC sample prepared in Example 4 has certain application potential, it is not as good as the sample in Example 3 in terms of breakdown strength.

Claims

1. A high-voltage MLCC ceramic powder for automotive use, characterized in that: It is made of the following raw materials: Nano powder, Nano powder and doping material, wherein the doping material includes lithium fluoride, magnesium oxide, silicon dioxide, manganese tetraoxide, yttrium oxide, ytterbium oxide and vanadium pentoxide.

2. The high-voltage MLCC ceramic powder for vehicle use according to claim 1, characterized in that: The amount of lithium fluoride added is 4 to 6 mol%.

3. The high-voltage MLCC ceramic powder for vehicle use according to claim 1, characterized in that: The added amount of the magnesium oxide is 4 to 6 mol%.

4. The high-voltage MLCC ceramic powder for vehicle use according to claim 1, characterized in that: The added amount of silicon dioxide is 1 to 3 mol%.

5. The high-voltage MLCC ceramic powder for vehicle use according to claim 1, characterized in that: Satisfy one or more of the following conditions: (1) the amount of manganese tetraoxide added is 0.1 to 0.3 mol%; (2) the amount of yttrium oxide added is 1 to 3 mol%; (3) the amount of ytterbium oxide added is 1 to 3 mol%; (4) the amount of vanadium pentoxide added is 0.1 to 0.3 mol%; (5) The amount of nanopowder added is 1 to 3 mol%; (6) The addition amount of nano powder is 80-90 mol%.

6. The high-voltage MLCC ceramic powder for vehicle use according to claim 1, characterized in that: Meet one or more of the following conditions: (1) The nanopowder is prepared by the following method: calcium nitrate tetrahydrate and tetraisopropyl titanate are mixed in a molar ratio of 1:1, deionized water is added, and the precursor liquid is stirred evenly to form a precursor liquid; the precursor liquid is transferred to an autoclave, reacted at 200°C for 12 hours, cooled after the reaction, centrifuged, and washed; and then dried at 80°C for 12 hours to obtain the Nano powder; (2) The nanopowder is prepared by the following method: four solutions A, B, C and D are prepared, wherein solution A is a solution of 2.5 grams of barium acetate dissolved in 50 milliliters of deionized water; solution B is a solution prepared by adding 5 grams of sodium hydroxide to 50 milliliters of deionized water; solution C is a solution of 2.83 grams of tetraisopropyl titanate dissolved in 50 milliliters of anhydrous isopropanol; solution D is a solution of 25 milliliters of oleic acid dissolved in 50 milliliters of anhydrous isopropanol; then, solution A and solution B are mixed, and the pH value of the mixed solution is adjusted to 14; then, solution C containing a titanium precursor is added dropwise to the above mixed solution; finally, solution D containing oleic acid is added to the mixed solution; after vigorous stirring, the mixture is transferred to an autoclave and reacted at 180°C for 16 hours; after the reaction is completed, the mixture is centrifuged, the precipitate is washed with ethanol, and then dried at 80°C for 12 hours to obtain the nanopowder. Nano powder.

7. A method for preparing high-voltage MLCC ceramic powder for vehicle use, characterized in that: It includes the following steps: (1) Nanopowders and The nanopowders are mixed and then doping materials are added to form a mixed powder; the mixed powder is then placed in an oven and pre-dried at 80°C for 12 hours to obtain a pre-dried mixed powder; (2) the obtained pre-dried mixed powder, zirconium oxide balls and anhydrous ethanol are mixed in a weight ratio of 1:6:3, and ball milled on a planetary ball mill; the ball milling time is 24 hours and the rotation speed is 300 r / min; the slurry obtained after ball milling is vacuum dried at 100°C for 12 hours to obtain a dry high-voltage MLCC ceramic powder; wherein the doping materials include lithium fluoride, magnesium oxide, silicon dioxide, manganese tetraoxide, yttrium oxide, ytterbium oxide and vanadium pentoxide.

8. A multilayer ceramic capacitor, characterized in that: It is obtained by sintering the high-voltage MLCC ceramic powder for vehicle use as described in any one of claims 1 to 6.

9. The multilayer ceramic capacitor according to claim 8, wherein: The multilayer ceramic capacitor is made by sintering the high-voltage MLCC ceramic powder for vehicle use and a metal inner electrode; wherein the sintering temperature is 1150°C to 1250°C, the sintering time is 2 to 4 hours, the thickness of the dielectric layer is 6 to 8 μm, and the number of layers is 100 to 140.

10. A high-voltage MLCC ceramic powder for vehicle use as claimed in any one of claims 1 to 6, applied to a vehicle electronic system.

Citation Information

Patent Citations

  • Ceramic dielectric ceramic powder and preparation method and application thereof

    CN112723876A

  • Middle-high voltage X7R type dielectric ceramic material

    CN119430912A

  • Nano doping dielectric material for preparing base-metal inner-electrode multi-layer ceramic sheet type capacitor

    CN101182201A

  • Medium material for high-reliability X8R-type multilayer ceramic capacitor and preparation method thereof

    CN105174941A

  • Medium material used for ceramic capacitor and preparation method thereof

    CN107840654A